How to read journal articles in the social sciences : a very practical guide for students - Shon, Phillip Chong Ho (Sage study skills, 2012)
"Using a reading code sheet developed by the author, this book teaches students how to approach social and behavioral science journal articles as texts that can be deciphered structurally, mechanically, and grammatically. The included reading code sheet and reading strategies will allow students and researchers to systematize the reading, note-taking, and organizing of voluminous amounts of information in an easily identifiable and retrievable format, and will be a huge confidence boost to those who struggle with this first phase in the writing process."--pub. desc.